Rehabilitation treatment of multiple sclerosis - Duan, Haoyang; Jing, Yuling; Li, Yinghua; Lian, Yawen; Li, Jianfang; Li, Zhenlan (Frontiers in Immunology, 2023)
Multiple sclerosis is a slowly progressive disease, immunosuppressants and other drugs can delay the progression and progression of the disease, but the most patients will be left with varying degrees of neurological deficit symptoms, such as muscle weakness, muscle spasm, ataxia, sensory impairment, dysphagia, cognitive dysfunction, psychological disorders, etc. From the early stage of the disease to the stage of disease progression, professional rehabilitation treatment can reduce the functional dysfunction of multiple sclerosis patients, improve neurological function, and reduce family and social burdens. With the development of various new rehabilitation technologies such as transcranial magnetic stimulation, virtual reality technology, robot-assisted gait, telerehabilitation and transcranial direct current stimulation, the advantages of rehabilitation therapy in multiple sclerosis treatment have been further established, and more treatment means have also been provided for patients.